NSAIDs in the Treatment of Postoperative Pain - Gupta, Anita; Bah, Maimouna (Current pain and headache reports, 2016)
Purpose of Review Postoperative pain results in multiple undesirable physiologic and psychological outcomes, and it should be managed in a multimodal approach. This article reviews the latest scientific literature of NSAIDs in the treatment of postoperative pain. The goal is to answer the following questions: (1) Are NSAIDs effective in the postoperative period? (2) Are NSAIDs safe in all surgical patients? and (3) Are adverse effects of NSAIDs increased or diminished in the acute postoperative period? Recent Findings NSAIDs are safe and effective in the treatment of postoperative pain, and they should be administered to all postoperative surgical patients unless contraindicated. Summary Based on literature, NSAIDs have been shown to increase patient satisfaction and decrease opioid requirements, minimizing opiate-induced adverse events. They have no increased incidence of adverse effects during the acute postoperative period. NSAIDs and COX-2 inhibitors, however, should be used with caution in colorectal surgery as they are proven to increase the risk of anastomotic leak.